The Influence of Financial Technology on the Reformulation of Bank Customer Protection Regulations. - Andri Brawijaya; Henny Nuraeny; Nova Monaya (Ann Publisher, 2025)
Background. The rapid evolution of financial technology has shifted banking activities toward fully digital environments, creating new opportunities for efficiency while simultaneously exposing customers to broader and more complex risks. Traditional regulatory frameworks, originally designed for conventional banking, often struggle to address issues arising from digital transactions, data processing, and emerging online service models. This situation has prompted regulators and financial institutions to reconsider existing norms to ensure stronger and more adaptive customer protection. Aim. This study aims to examine how technological developments influence regulatory reform in order to strengthen the protection of bank customers. Methods. A qualitative approach is applied through systematic analysis of regulatory developments, institutional policies, and emerging patterns of consumer risk in digital banking. Results. The study finds that technological growth drives regulators to refine customer protection rules, especially in areas related to customer rights, digital accountability, and data security. Banks also adopt updated internal policies to meet evolving regulatory expectations. Conclusions. Financial technology plays a significant role in encouraging regulatory reform, pushing authorities toward more adaptive and forward-looking frameworks. Implication. Continuous regulatory development is essential to ensure that customer protection remains effective as digital financial services continue to advance. Keywords: Financial technology; customer protection; banking regulation; digital banking; regulatory reform.